Uma abordagem tripartida do dialogismo na leitura de A jangada de pedra, O Evangelho segundo Jesus Cristo e Ensaio sobre a cegueira, de José Saramago - Wertheimer, Ana Maria Coelho Silva (2018)
This thesis proposes a tripartite approach to dialogism for the analysis of three novels by José Saramago (1922-2010), namely, A jangada de pedra, O Evangelho segundo Jesus Cristo and Ensaio sobre a cegueira, which were selected by the reason that they approach political, religious and social issues, respectively. Based on the theories of Mikhail Bakhtin (1895-1975), whose intellectual production lasted for about sixty years – which may justify the use of the term dialogue in different contexts and with distinct concepts –, this study is guided by three possible meanings within dialogism: the dialogue in the theory of language, the dialogue in the novel and the dialogue in the genre memory. Without ignoring the vast critical reviews of the Portuguese writer’s work, this thesis intends to answer a question: how are dialogic relationships established in Saramago's novels? Searching for an answer, a second, more complex question arises: is it possible that the dialogic relationships in the narrative structure of Saramago’s characters and narrator represent his process of literary creation? The hypothesis is that the artistic form of the writer represents, besides a tendency, a renewal of the genre itself. This study is, therefore, divided into three parts: the first is dedicated to the dialogue at the level of language, regarding the ideological sense of the linguistic sign and the different types of the reported speech; the second part approaches the dialogue in the novel, focusing on the plurilingual and polyphonic features of the discourse in the novel; and the third part, in the sphere of the memory of the genre, investigates aspects of carnival literature and chronotopic structures that constitute the narratives. It is added to this study the ideas of researchers such as Michael Holquist, Gary Saul Morson, Caryl Emerson and, from Brazil, Irene Machado, Beth Brait, Carlos Alberto Faraco, and Cristovão Tezza, among others who seek to understand and systematize Bakhtin’s concepts. It is expected that a study that examines Saramago's writing can contribute both to a reflection on his creative process and also to a (re)reading of Bakhtin's dialogic principle in Literature.